The Impact of Dark Chocolate on Health, Culture, and Industry, and Identifying Knowledge Gaps for Future Research - Mr. Rushikesh Bhaskar Mehankar; Dr. Neha N. Rajpurohit (International Journal of Scientific Research in Science and Technology, 2024)
This study asks us to do a comprehensive review of dark chocolate, including its nutritional value, potential health benefits, and culinary uses. The analysis begins by classifying chocolate according to the amount of cocoa and chocolate content, such as cocoa thickness, cocoa butter, emulsifiers This shows us the unique nutritional value of dark chocolate, including high dietary fiber, minerals and includes flavonoids Dark chocolate cardiovascular health and general well-being There are benefits, but There are also drawbacks to overeating, including high calorie intake and health problems The study identifies market trends and consumer preferences, indicating increased demand for cocoa-rich products and ethical derivatives The study concludes with research gaps and health risks of the expression of specific chemicals. Of influences, of regular cocoa, of dark chocolate Further research gives us an idea of influences and Different factors influencing health. The ultimate goal of this study is to better understand dark chocolate as a functional food that balances pleasure and responsible consumption.
Keywords: Dark Chocolate; health benefits; Market trends; functional food